2018
DOI: 10.1002/eji.201847668
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab dampens type 2 inflammation in a group of long‐term treated asthma patients and detaches IgE from FcεRI

Abstract: Even if omalizumab is broadly used in the treatment of severe, allergic asthma, the immunological effects in long-term treated patients have not been fully elucidated. To this aim, a cohort of 15 allergic asthmatic patients treated with omalizumab for at least three years was compared with 12 allergic asthma patients treated with standard therapy. Omalizumab treated asthmatic patients showed lower frequencies of circulating plasmacytoid DCs, and lower CD154 expression on CD4 T-helper cells than the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
3
36
0
1
Order By: Relevance
“…Recent studies confirmed that a long-term treatment with omalizumab reduces type 2 inflammation by acting on different types of cells that play a fundamental role in the pathogenesis of allergic asthma but also thanks to the ability to detach IgE from its receptor. 70 In the EXTRA study, the subpopulation with atopy with PBE ≥ 260 cells/μL and FeNO ≥ 19.5 ppb is associated with an increased probability of response to omalizumab. 71 Based on available evidence, the combination of presence of total serum IgE within the dosage range, a history of frequent exacerbations, persistent asthma symptoms, decrease in FEV 1 , allergen specific IgE for perennial inhalants, increase in FeNO and increase in PBE is associated with an increased likelihood of response to omalizumab.…”
Section: Methodsmentioning
confidence: 98%
“…Recent studies confirmed that a long-term treatment with omalizumab reduces type 2 inflammation by acting on different types of cells that play a fundamental role in the pathogenesis of allergic asthma but also thanks to the ability to detach IgE from its receptor. 70 In the EXTRA study, the subpopulation with atopy with PBE ≥ 260 cells/μL and FeNO ≥ 19.5 ppb is associated with an increased probability of response to omalizumab. 71 Based on available evidence, the combination of presence of total serum IgE within the dosage range, a history of frequent exacerbations, persistent asthma symptoms, decrease in FEV 1 , allergen specific IgE for perennial inhalants, increase in FeNO and increase in PBE is associated with an increased likelihood of response to omalizumab.…”
Section: Methodsmentioning
confidence: 98%
“…In this view, the low number of these cells may be considered as a cellular biomarker of low risk of exacerbations and of good disease control. 71 Last but not least, it should be mentioned that treatment with omalizumab has great treatment potential in conditions with evidently non-allergic aetiology, such as chronic idiopathic urticaria resistant to therapy with antihistamines 73 and to chronic rhinosinusitis with nasal polyps (CRSwNP). 74 At present, two phase III studies have been registered at ClinicalTrials.gov, NCT03280550 (POLYP 1) and NCT03280537 (POLYP 2) with extension NCT03478930.…”
Section: Possibilities Of Targeted Therapeutic Affecting Of Ige Actionmentioning
confidence: 99%
“…The mechanisms by which omalizumab exerts its beneficial effects range from the neutralizing activity on soluble IgE to the capacity to downregulate FcεRI on basophils and mast cells. More recently it has also been demonstrated the ability of omalizumab to dissociate prebound IgE from the high affinity receptor on basophils, thus reducing basophils’ allergen‐dependent degranulation capacity . Nevertheless, about one third of the potentially responder patients, fail to benefit from the treatment, and the reasons are not fully elucidated.…”
Section: Asthmamentioning
confidence: 99%
“…Indeed, it is well known that omalizumab treatment, in responder patients, determines an increase of serum IgE, since standard IgE assays is able to detect both free and omalizumab‐complexed IgE . This increase in total IgE levels has been associated to the longer half‐life of omalizumab‐complexed IgE compared to free IgE , but probably also other mechanisms are involved in this paradoxical increase . Indeed, beyond the well‐known ability of omalizumab to capture free IgE preventing the activation of basophils, mast cells, and dendritic cells (DCs), and to reduce FcεRI expression on these cells, the capacity to dissociate prebound IgE from high‐affinity Fcε receptor on basophils, has recently emerged as a novel mechanism of action .…”
Section: Chronic Spontaneous Urticariamentioning
confidence: 99%
See 1 more Smart Citation